Learning Strategies at SD Muhammadiyah 1 Krembung During the Covid-19 Pandemic - Ajeng Nurmadi Cahyanti; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this study is to examine strategies at SD Muhammadiyah 1 Krembung for learning during the Covid-19 pandemic. In the research process, this time using data collection techniques through interviews, observation, and documentation when the research process was carried out. This study aims to reveal and conclude the early history of the establishment of SD Muhammadiyah 1 Krembung in Lemujud Village. In terms of background and excellent programs. Besides that, there are several strategies that have been carried out. Such as in the process of implementing learning, internet quotas, student morals, and others. However, SD Muhammadiyah 1 Krembung continues to carry out its programs and activities with the hope that SD Muhammadiyah 1 Krembung can develop more advanced and its students become graduates with noble morals.